Students Scientific Literacy Profile of Mathematics Education Study Program in Chemistry Subjects - Natalia Peni; Melania Priska; Yosephina Payu Wao (Postgraduate, University of Mataram, 2022)
This study aims to describe the scientific literacy profile of students in the mathematics education study program in chemistry subjects. The research method is descriptive quantitative research, with the research subject being the second semester students of the Mathematics Education Study Program at the University of Flores in 2021/2022 academic year, totaling 29 peoples. The data resource from the questionnaires, which was based on the aspect of competence. Furthermore, the scientific literacy student competency test questions were tested for validity and reliability, then continued with a final score test to interpret descriptively student learning outcomes. The results of the scientific literacy profile of prospective teachers mathematics at the Faculty of Teacher Training and Education,Â Flores University consist of 5 indicators, namely, identifying and explaining scientific phenomena, getting a score of 75.45, which is good category; Â evaluating and designing scientific questions, getting score of 55.75, which is reasonable category; interpreting data and evidence scientifically, getting a score of 62.25 which is reasonable category; creating a good graph, getting a score of 57.55 which is reasonable category; problem-solving skills, getting a score of 60.25 which is reasonable category; understanding and interpreting data, getting a score of 45.00 which is very much less category; and the ability to draw conclusions, getting a score of 77.00 which is good category. These results performed that scientific literacy skills of students are reasonable category.